Advances in Diptera Insight, Challenges and Management Tools - Kumar, Sarita (IntechOpen, 2022)
This volume, Advances in Diptera - Insight, Challenges and Management Tools, highlights the biology, life stages, physiology, and significance of dipteran flies. Their importance as agricultural pests and disease vectors, and their management using various conventional and advanced tools is examined. Each of the five chapters covers a significant aspect in the field of diptera, including the physiology of dipteran diapause, the biology and management of mosquitoes using various traditional and innovative approaches, and the bionomics of onion, garlic and walnut pests. We hope that this book will interest students and researchers, and help them to recognize potential research areas.